Ischaemic stroke as the presenting feature of COVID-19: a series of three cases from Qatar. Issue 3 (8th March 2021) - Iqbal, Yousaf; Haddad, Peter M; Latoo, Javed; Alhatou, Mohammed Ibrahim; Alabdulla, Majid
Abstract: Most cases of stroke associated with coronavirus disease 2019 (COVID-19) occur during the course of a characteristic COVID-19 respiratory illness. We report three patients where the presenting feature of COVID-19 was stroke. Two patients had no respiratory symptoms throughout their clinical course. In each case, COVID-19 was confirmed by a reverse transcription polymerase chain reaction (RT-PCR) test and the diagnosis of ischaemic stroke by brain imaging. The patients were relatively young (40, 45 and 50 years). None had a prior history of cerebrovascular events. Stroke risk factors were absent in one, limited to overweight and smoking in another but more prominent in the third patient. Two patients had large vessel occlusion and elevated D-dimer levels. Multiple infarcts were seen in two patients. Clinicians should consider the possibility of COVID-19 in patients presenting with stroke and conversely consider investigating for stroke if a patient with COVID-19, even if mildly ill, develops acute neurological symptoms.